Environmental, Social, Governance (ESG) and Islamic Finance: A Review - Abdillah Arif Nasution; Darwis Harahap; Mimma Maripatul Uula (SMART Insight, 2022)
This study aims to look at the development of research on Environmental, Social, Governance (ESG) and Islamic finance and research path that can be carried out based on journals published on this theme. This study used a qualitative method with a bibliometric analysis approach. The data used is secondary data with the theme